2022
DOI: 10.1002/ajpa.24507
|View full text |Cite
|
Sign up to set email alerts
|

Morphological correlates of distal fibular morphology with locomotion in great apes, humans, and Australopithecus afarensis

Abstract: Objectives Recent studies highlighted the importance of the fibula to further our understanding of locomotor adaptations in fossil hominins. In this study, we present a three‐dimensional geometric morphometric (3D‐GM) investigation of the distal fibula in extant hominids and Australopithecus afarensis with the aim of pointing out morphological correlations to arboreal behavior. Methods Three‐dimensional surface meshes of the distal fibula were obtained using computer tomography for 40 extant hominid specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 100 publications
4
12
0
Order By: Relevance
“…The aim of this study was to highlight patterns of sexually dimorphic form variations in the fibular proximal and distal epiphyses in individuals of three different populations from Italy and South Africa belonging to identified modern skeletal collections (19th–20th century), utilizing a 3D GM approach [ 54 ]. Our study provides a new method for sex estimation on the fibula, potentially applicable in bioarcheology [ 20 ], where this method may find primary implementation, and forensics, offering moderate to high accuracy (80–93% for Italian populations) for identification in case of the recovery of isolated fragments of this bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to highlight patterns of sexually dimorphic form variations in the fibular proximal and distal epiphyses in individuals of three different populations from Italy and South Africa belonging to identified modern skeletal collections (19th–20th century), utilizing a 3D GM approach [ 54 ]. Our study provides a new method for sex estimation on the fibula, potentially applicable in bioarcheology [ 20 ], where this method may find primary implementation, and forensics, offering moderate to high accuracy (80–93% for Italian populations) for identification in case of the recovery of isolated fragments of this bone.…”
Section: Discussionmentioning
confidence: 99%
“…While the specific relationship between a muscle and its tendon can change depending on several factors (e.g., muscle/tendon specificity, loading degree, age), in our sample, such variations are minimal, since all individuals possess similar activity levels (i.e., sedentary lifestyle [ 76 ], and age variations in the samples are similar ( Table 1 ). Therefore, tendon size could be used to assess muscle size [ 54 ]. Finally, we did not find significant shape/form sex-related variation regarding articular orientation in agreement with previous studies on sex variations of the bones of the leg [ 28 ], but see also [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…A template of 142 landmarks and semilandmarks (Table 1 and Figure 1 ), modified from a previous version published by Marchi et al ( 2022 ), was applied to targets (both CT‐ and laser scanner‐generated models) utilizing Viewbox 4 software (dHal Software). Curve and surface semilandmarks were allowed to slide along the curves/surfaces to minimize the thin‐plate spline (TPS) bending energy between the target and the template obtaining geometrically homologous semilandmarks (Slice, 2005 ; Gunz & Mitteroecker, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we test the accuracy and comparability of CT‐ and laser scanner‐generated meshes in a sample of 13 modern human fibulae, considering the whole bone surface but also focusing on the extremities. The fibula has so far not been included in previous mesh accuracy assessments, despite its digitization in several biomechanical studies, alongside the tibia (e.g., Marchi, 2005 , 2007 , 2015b ; Marchi, 2015a ; Marchi et al, 2019 , 2022 ). In addition, fibular 3D meshes are routinely utilized in reconstructive surgery, in the assessment of tibio‐fibular syndesmotic reductions performed after ankle fractures (e.g., Ebinger et al, 2013 ; Souleiman et al, 2021 ) and surgical planning of mandibular reconstructions from fibular free flaps (e.g., Damecourt et al, 2020 ; Ni et al, 2021 ; Ren et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that all great apes separate from one another (Figure 6) due to distinctive proximal fibular morphology. Previous studies found significant differences in relative (to the tibia) fibular strength (Marchi, 2007(Marchi, , 2015a and distal fibular morphology (Marchi et al, 2022) among taxa that engage more frequently in vertical climbing behavior (Pan and Pongo) compared to those that are more terrestrial (Homo and Gorilla). The authors linked these differences to larger peroneal muscles in the former, a feature that has generally been associated with arboreal great apes (Aiello & Dean, 1990;McLean & Marzke, 1994;.…”
Section: Differences Among Great Apesmentioning
confidence: 96%